A follow‐up survey of knowledge, attitudes and practices surrounding blood donation in Trinidad and Tobago. (25th May 2017) - Charles, K. S.; Chisholm, K.; Gabourel, K.; Philip, K.; Ramdath, S.; Abdul‐Hakeem, H.; Vaillant, A.; Pooransingh, S.; Legall, G.; Chantry, A.
Abstract : Background and objectives: Trinidad and Tobago is a multi‐ethnic, multicultural country with an annual blood donation rate of 17 per 1000 and predominantly (87%) family/replacement (F/R) donors. A knowledge, attitudes and practice (KAP) community survey in 2003 revealed lack of information and poor access to donation centres as barriers to voluntary non‐remunerated donors (VNRD). The survey was repeated in 2013 after a national intervention to increase VNRD failed. Materials and methods: The second cross‐sectional, questionnaire‐based survey was administered to 816 adults in the same community. The variables assessed were sociodemographics, knowledge, attitudes and blood donation behaviour. Data analysis was performed using SPSS statistical software and Minitab 17. Chi‐square was used to assign significance and logistic regression to analyse correlation between variables. Results of the two surveys were compared. Results: There was no difference in the overall percentage of donors (18·8 vs. 21·1%, P = 0·337), and a low donor percentage was observed in all sociodemographic groups (7·7–31·6% vs. 10·2–31·7%). The main reason for donating blood was replacement for a relative or friend (86·0 vs. 86·9% P = 0·851). Willingness to repeat donation was high (90·6% vs. 86·4%, P = 0·006). Motivators and demotivators to donation varied among sociodemographic groups. Conclusion: There was no significant change in community KAP between surveys. Anthropological studies into blood donation are needed to plan an effective revised and targeted blood donation campaign. Legal and regulatory changes must facilitate VNRD.